2013
DOI: 10.14260/jemds/1313
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Study on Oligohydramnios in the Third Trimester of Pregnancy With Special Emphasis on the Perinatal Outcome

Abstract: The above study was conducted to find out the perinatal outcomes in pregnancies with oligohydramnios, especially in the third trimester of pregnancy. METHODS: This prospective and observational study was conducted in a Medical college and research centre at Moradabad city, U. P, from January to December 2012. In this study 78 singleton pregnant women with gestational age from 28-42 weeks with less amniotic fluid index (AFI) were analyzed for perinatal outcome. Data were expressed as number (percentage). Propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
2
6
1
Order By: Relevance
“…In our study also the main cause for LSCS was fetal distress as indicated by NRNST, although 27% had MSL, the indication for CS among MSL was present in only 11.1%. (8) In another study, among pregnancy with AFI<5, nonreassuring Fetal heart rate was observed in 6%, which was much higher in our study, while the percentage of neonatal requiring NICU admission was 20% whilst 6% in our study. (9) The rate of NICU admission was also very high recorded up to 43%.…”
Section: Resultscontrasting
confidence: 43%
“…In our study also the main cause for LSCS was fetal distress as indicated by NRNST, although 27% had MSL, the indication for CS among MSL was present in only 11.1%. (8) In another study, among pregnancy with AFI<5, nonreassuring Fetal heart rate was observed in 6%, which was much higher in our study, while the percentage of neonatal requiring NICU admission was 20% whilst 6% in our study. (9) The rate of NICU admission was also very high recorded up to 43%.…”
Section: Resultscontrasting
confidence: 43%
“…6 Nath J et al showed hepatic encephalopathy as a major complication present in 17% of cases which is 5.71% in present study. 7 In present study, maternal mortality was 9/70(12.85%) however jaundice was responsible for 13.23% death of the 68 deaths that occurred in our department during study period. In the study highest mortality was due to DIC associated with multiorgan failure, septicemia, hepatic encephalopathy, pulmonary oedema and acute fulminant hepatic failure accounting for 7.14% of the total cases.…”
Section: Resultsmentioning
confidence: 43%
“…Similar results were found in studies by Nazlima et al who noted an APGAR score of < 7 at 5 min in 26.9% and Jayati Nath et al who reported APGAR score < 7 at 5 min in 26 %. 3,7 Amount of liquor (clinical judgement)…”
Section: Apgar Scorementioning
confidence: 99%